2015
DOI: 10.1007/s13277-015-3655-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hesperidin on mice bearing Ehrlich solid carcinoma maintained on doxorubicin

Abstract: Doxorubicin (DOX) is widely used in cancer therapy of many carcinomas types. Unfortunately, DOX is not sufficiently effective in many cases, and increasing the dosage of it is limited due to its systemic toxicity. A citrus flavonoid hesperidin (HES) is proved to be potent antioxidant and protective agent against many diseases including cancer. In this context, the objective of this study was to examine effect of HES along with DOX on solid Ehrlich carcinoma (SEC) in mice. Forty male mice were divided into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 37 publications
6
12
0
Order By: Relevance
“…However, decrease in MDA and increase in SOD levels was observed in the HSPpretreated group. This could be attributed to the antioxidant properties of HSP against oxidative stress which is consistent with other studies that have reported protective role of HSP against oxidative stress [55][56][57][58][59]. HSP also inhibits oxidative stress and inflammation in ultraviolet B irradiation-induced skin damage in mice [60].…”
Section: Discussionsupporting
confidence: 89%
“…However, decrease in MDA and increase in SOD levels was observed in the HSPpretreated group. This could be attributed to the antioxidant properties of HSP against oxidative stress which is consistent with other studies that have reported protective role of HSP against oxidative stress [55][56][57][58][59]. HSP also inhibits oxidative stress and inflammation in ultraviolet B irradiation-induced skin damage in mice [60].…”
Section: Discussionsupporting
confidence: 89%
“…37 Furthermore, Cruet-Hennequart et al 38 reported that DOX decreased DNA content in cultured human mesenchymal stem cells and in mammary gland carcinoma. 39 The anticancer effect of MET and DOX, as observed in this study, was associated with significant increase in P53 with induction of apoptosis. Histopathological findings showed that treatment of SEC mice with various treatments increased apoptotic cell count which was significant in co-treatment group rather than mono-treatment groups.…”
Section: Discussionsupporting
confidence: 64%
“…37 Furthermore, Cruet-Hennequart et al 38 reported that DOX decreased DNA content in cultured human mesenchymal stem cells and in mammary gland carcinoma. 39…”
Section: Discussionmentioning
confidence: 99%
“…Tumor volume (mm 3 ) [ 87 ] and body weight were measured every 7 days until animals were anesthetized and sacrificed. After two weeks of treatment, all mice were euthanized under anesthesia via Matrx VMS anesthesia machine (Midmark Corporation) by continuous inhalation of CO 2 , 2% isoflurane gas for 5–10 min, Tumor inhibition rate (%) was determined [ 88 ].…”
Section: Methodsmentioning
confidence: 99%